Design and Development of a Web-Based Plastic Waste Recycling Information System case study: Bali Pet Collection Center - Astika, I Putu Jordi; Githa, Dwi Putra; Darma Putra, I Ketut Gede (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2023)
A plastic recycling company is an industry that specializes in recycling plastic waste into processable plastic pellets. The current business process still relies on conventional methods for recording activities within the company. The objective of this research is to design and develop a web-based information system for plastic waste recycling. The waterfall methodology employed as the software development method. The system is tested using black box testing and user acceptance testing (UAT) and measured using Likert's summated Rating (LSR) method. The results of the black box testing indicate that the system functions well. Furthermore, the results of the UAT demonstrate that the system as a whole receives highly positive responses and is considered successful.